Self-work and social change: disindividualised participation amongst young Australian Buddhist practitioners. (9th August 2018) - Lam, Kim
ABSTRACT: Recent work on youth participation has mobilised a 'DIY' or 'individualised' framework to explain the nature of contemporary participation, particularly amongst minoritised religious youth. This paper examines this conceptual framework in light of concurrent claims that contemporary participation can be better conceptualised using a 'doing it with others' (DIWO) approach, which emphasises the collaborative nature of participation. In light of these claims, I analyse the participation experiences of 22 young adult Buddhist practitioners who are located within a neo-liberal Australian context, yet simultaneously have access to religious teachings and practices which challenge distinct notions of selfhood. This paper shows that both 'DIY' and 'DIWO' conceptions of participation find expression in the participation experiences of participants from the study, and that both DIY and DIWO approaches can additionally be seen as mutually reinforcing rather than distinctly contrasting. I propose a new concept of 'disindividualisation', suggesting that Maffesoli's concept of 'disindividuation' and Elias's work linking psychological development and social change should be considered in conjunction with an individualised or DIY perspective on youth participation to denote this kind of participatory work.